PHARMACO-ECONOMIC COMPARISON OF ENOXAPARIN AND UNFRACTIONATED HEPARIN IN ACUTE CORONARY SYNDROME WITHOUT ST SEGMENT ELEVATION - A. V. Syrov; S. K. Zyryanov; Yu. B. Belousov (Российский кардиологический журнал)
Acute coronary syndrome (ACS) is a form of coronary heart disease (CHD), combining acute myocardial infarction with ST segment elevation (STE ACS), acute myocardial infarction without ST segment elevation, and unstable angina (non-STE ACS). These clinical forms are considered as one syndrome, due to a high risk of acute myocardial infarction and sudden coronary death. Therefore, the problem of ACS treatment is particularly important. The management of non-STE ACS should always include anticoagulants – specifically, enoxaparin or unfractionated heparin. This study was aimed at identifying the anticoagulant with the best clinical and pharmaco-economic characteristics in conservative treatment of non-STE ACS.